2013
DOI: 10.2337/db12-1747
|View full text |Cite
|
Sign up to set email alerts
|

X-Box Binding Protein 1 Is Essential for Insulin Regulation of Pancreatic α-Cell Function

Abstract: Patients with type 2 diabetes (T2D) often exhibit hyperglucagonemia despite hyperglycemia, implicating defective α-cell function. Although endoplasmic reticulum (ER) stress has been suggested to underlie β-cell dysfunction in T2D, its role in α-cell biology remains unclear. X-box binding protein 1 (XBP1) is a transcription factor that plays a crucial role in the unfolded protein response (UPR), and its deficiency in β-cells has been reported to impair insulin secretion, leading to glucose intolerance. To evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 50 publications
3
59
0
Order By: Relevance
“…In support of this conclusion, XBP1-deficient cells have reduced AKT phosphorylation without changes in PTEN expression compared with JunB KD cells. XBP1 has been shown to modulate AKT activity in other cell types, 31,42 and XBP1 may directly bind PI3K, facilitating AKT phosphorylation in endothelial cells. 43 JunB may also modulate AKT phosphorylation through a XBP1-dependent improvement of the ER folding capacity and consequent restoration of mTOR or via inhibition of protein phosphatase 2A, two important pathways previously shown to regulate AKT.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this conclusion, XBP1-deficient cells have reduced AKT phosphorylation without changes in PTEN expression compared with JunB KD cells. XBP1 has been shown to modulate AKT activity in other cell types, 31,42 and XBP1 may directly bind PI3K, facilitating AKT phosphorylation in endothelial cells. 43 JunB may also modulate AKT phosphorylation through a XBP1-dependent improvement of the ER folding capacity and consequent restoration of mTOR or via inhibition of protein phosphatase 2A, two important pathways previously shown to regulate AKT.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with alpha cell-specific disruption of XBP1 expression (alpha-XBP1KO) [140] exhibit altered glucagon secretion as a result of increased ER stress that is not directly associated with alpha cell mass or growth. Surprisingly, prolonged XBP1 overproduction in rat islet cells impaired glucose-stimulated insulin secretion, BAX (BCL2-associated X protein) translocation, cytochrome c release and activation of caspase 3 and beta cell apoptosis [141].…”
Section: Old Agementioning
confidence: 99%
“…It is worth noting that our data showed that IRE1α may modulate Akt phosphorylation through an XBP1 dependent manner as well. In fact, the regulatory role of XBP1s on Akt activity has also been reported in other cell types (33,34). Besides, an earlier study reported that in islets of db/db mice, increased activation of xbp1 mRNA was observed, presumably a compensatory mechanism to inhibit ER stress and β cell apoptosis induced by obesity (35).…”
Section: Discussionmentioning
confidence: 89%